Narratives of attachment in middle childhood: do gender, age, and risk-status matter for the quality of attachment?. Issue 6 (1st November 2016) - Gloger-Tippelt, Gabriele; Kappler, Gregor
ABSTRACT: Attachment in middle childhood increasingly attracts the interest of developmental psychologists and clinicians. Recent studies using attachment narratives elicited by story stems reported gender-specific aspects of attachment development, potentially evoked by developmental tasks during this period of the life span. There is evidence that children with risk factors present more insecure and disorganized attachment narratives compared to children without risk. Yet, there is little research concerning the joint effects of gender, risk, and age for attachment classifications. The paper presents a pooled analysis of 22 samples (eight risk samples) including 887 children (411 girls), aged between 4.5 and 8.5 years who were assessed with the same "German Attachment Story Completion Procedure" (GASCP). Girls were 1.8 times more likely to present secure and 0.4 times less likely to present disorganized narratives compared to boys when controlling for risk status and age. Children from risk samples were more likely (odd ratio 5.4) to display disorganized and less likely to show a secure attachment (odd ratio 0.3) compared to those from no-risk samples in multilevel logistic regressions. Remarkably, the effect of risk was not moderated by age and gender, and gender effects were not moderated by age.